Taxonomy of the fern genus Didymochlaena (Didymochlaenaceae) from Asia and Pacific islands based on morphological and molecular evidence with the description of four new species and one new status - Shang, Hui; Liang, Zhen-Long; Zhang, Li-Bing (Phytotaxa, 2021)
A taxonomic revision of Didymochlaena (Didymochlaenaceae) from Asia and the Pacific region is conducted based on morphological and molecular evidence. Seven species are recognized, of which four are described as new and a new status is raised to a species from a variety. These four new species include D. fijiensis from Fiji, D. philippensis from the Philippines, D. punctata from Indonesia, Malaysia, and Thailand, and D. solomonensis from the Solomon Islands. The new status is D. oceanica from Papua New Guinea. Six of the seven species have all been erroneously treated as D. truncatula by earlier pteridologists. A key to the species is provided and descriptions of all species are given.